Seorang Pemimpin Yang Besar (Tafsiran 1 Tawarikh 11:1-3) - Frischa Nofrianti; Remita Nian Permata Zendrato (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
In the future, theology students are expected to become good leaders for the church, society and the nation. Researchers study 1 Chronicles 11:1-3 to understand how King David became a great leader. This is a reflection for future theology students on what is meant by a great leader and how to be a good leader before God. Researchers used qualitative methods in completing this paper. Researchers hope that this article is useful for readers and adds insight.